Effect of the inclusion of different levels of probiotic on the productive parameters and intestinal morphology in fattening guinea pigs (Cavia porcellus) - Carcelén C., Fernando (2020)
The aim of this study was to evaluate the effect of increasing levels of probiotic as zinc-bacitracin substitutes in the productive performance and intestinal morphology of fattening guinea pigs. Fifty weaned male guinea pigs were randomly distributed into five treatments consisting of supplementation with 0, 1, 2 and 3 ml of the probiotic "Guinea Pig Biomodulator" and an additional treatment with zinc-bacitracin. Body weight gain, feed intake and feed conversion during 70 days of growth, and intestinal morphology variables: villus length and width, Lieberkühn crypt depth, and villus length/crypt depth ratio were evaluated in the duodenum, jejunum, and ileum. Increasing probiotic levels linearly improved (p=0.008) feed conversion rate but had no effect on the other productivity components. In the intestine, only the length/depth relationship in the ileum was positively affected (p=0.026) by the probiotic. It is concluded that there is no consistent effect of the probiotic on weight gain or on the intestinal morphology of fattening guinea pigs.